2005
DOI: 10.1007/bf03325839
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of petrol and diesel adulteration with kerosene and assessment of usefulness of selected automobile fuel quality test parameters

Abstract: Kerosene is common adulterant utilized for mixing with diesel. Five fuel-adulterant mixtures in different proportions by volume were prepared and individually tested for density and kinematic viscosity. The mixtures were administered to six light cargo vehicles and the tail pipe exhaust emission was tested for opacity value. No appreciable density variation at different levels of adulteration was observed. Density was within the prescribed value even at higher adulteration. Considerable decrease in kinematic v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
33
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 71 publications
(34 citation statements)
references
References 1 publication
0
33
0
1
Order By: Relevance
“…As seen in Table 1, increasing the concentration of kerosene in the blends decreases the density, calorific value, kinematic viscosity and cetane number of the blended fuel compared with neat diesel, but increases these values compared with neat kerosene. Yadav et al [16] have reported that no appreciable density variation at different levels of adulteration was observed, while a considerable decrease in kinematic viscosity was noted at higher adulteration levels of kerosene with diesel. …”
Section: Kerosene-diesel Blend Propertiesmentioning
confidence: 98%
See 3 more Smart Citations
“…As seen in Table 1, increasing the concentration of kerosene in the blends decreases the density, calorific value, kinematic viscosity and cetane number of the blended fuel compared with neat diesel, but increases these values compared with neat kerosene. Yadav et al [16] have reported that no appreciable density variation at different levels of adulteration was observed, while a considerable decrease in kinematic viscosity was noted at higher adulteration levels of kerosene with diesel. …”
Section: Kerosene-diesel Blend Propertiesmentioning
confidence: 98%
“…The experimental results showed that lower soot emissions were obtained with the kerosene-diesel blends at low load compared with neat diesel, while soot emission was similar to that of diesel fuel at high load; similar results were reported by Bergstrand [17].The variations of smoke, HC, NO x and CO for different BMEPs at 1500 rpm are shown in Figure 5. Yadav et al [16] have experimentally demonstrated that the percent opacity value decreased sharply even at a small adulteration level of kerosene with diesel. NO x refers to a class of compounds called nitrogen oxides, which usually represents a mixture of nitric oxide (NO) and nitrogen dioxide (NO 2 ).…”
Section: Emission Characteristicsmentioning
confidence: 99%
See 2 more Smart Citations
“…The term DPK stem from the fact that the product can be used both as an aviation fuel and for domestic purposes (cooking) this is slightly different from HHK (Household Kerosene) which is basically used for domestic purposes (Gupta et al, 1992). Mixing specific amount of DPK with AGO does not lead to an increase in tailpipe emission but contributes to air pollution however high level adulteration could have adverse effects on compression ignition engines (Yadav et al, 2005). Unlike PMS, diesel engines do not use high voltage spark ignition plugs but compression ignition stroke (Mishra et al, 2008).…”
Section: Introductionmentioning
confidence: 99%